Deletion of MicroRNA-144/451 Cluster Aggravated Brain Injury in Intracerebral Hemorrhage Mice by Targeting 14-3-3ζ - Wang, Xiaohong; Hong, Yin; Wu, Lei; Duan, Xiaochun; Hu, Yue; Sun, Yongan; Wei, Yanqiu; Dong, Zhen; Wu, Chenghao; Yu, Duonan; Xu, Jun (Frontiers in Neurology, 2021)
This study aims at evaluating the importance and its underlying mechanism of the cluster of microRNA-144/451 (miR-144/451) in the models with intracerebral hemorrhage (ICH). A model of collagenase-induced mice with ICH and a model of mice with simple miR-144/451 gene knockout (KO) were used in this study. Neurodeficits and the water content of the brain of the mice in each group were detected 3 days after collagenase injection. The secretion of proinflammatory cytokines, such as tumor necrosis factor α (TNF-α) and interleukin 1β (IL-1β), as well as certain biomarkers of oxidative stress, was determined in this study. The results revealed that the expression of miR-451 significantly decreased in the mice with ICH, whereas miR-144 showed no significant changes. KO of the cluster of miR-144/451 exacerbated the neurological deficits and brain edema in the mice with ICH. Further analyses demonstrated that the KO of the cluster of miR-144/451 significantly promoted the secretion of TNF-α and IL-1β and the oxidative stress in the perihematomal region of the mice with ICH. In addition, the miR-144/451's depletion inhibited the regulatory axis' activities of miR-451-14-3-3ζ-FoxO3 in the mice with ICH. In conclusion, these data demonstrated that miR-144/451 might protect the mice with ICH against neuroinflammation and oxidative stress by targeting the pathway of miR-451-14-3-3ζ-FoxO3.